Hybrid anxieties : queering the French-Algerian War and its postcolonial legacies - Quinan, C. L. (Expanding frontiers., 2020)
"Hybrid Anxieties utilizes literature and film as a means to investigate the ways in which the French-Algerian War and its postcolonial legacies have precipitated a crisis in gender and sexuality"--